Respostas

2014-07-17T19:16:00-03:00
E aí Nerd1,

use as propriedades da exponenciação:

(a^m)^n~\to~a^{m*n}~\to~a^{mn}\\\\
 \dfrac{1}{a}~\to~ \dfrac{1}{a^1}~\to~a^{-1}

________________________

\begin{cases}(3^x)^{x-4}= \dfrac{1}{27}\\\\
\not3^{ x^{2} -4x}=\not3^{-3}\\
 x^{2} -4x=-3\\
 x^{2} -4x+3=0\\\\
x'=1~~e~~x''=3\\\\
\boxed{S=\{1,3\}}\end{cases}\begin{cases}\left( \dfrac{1}{4}\right)^{x-1}=16^{x-2}\\\\
(2^{-2})^{x-1}=(2^4)^{x-2}\\
\not2^{-2x+2}=\not2^{4x-8}\\
 -2x+2=4x-8\\
-2x-4x=-8-2\\
-6x=-10\\\\
x= \dfrac{-10}{-6}\\
x= \dfrac{5}{3}\\\\
\boxed{S=\left\{ \dfrac{5}{3}\right\}}\end{cases}

Tenha ótimos estudos (y)
1 1 1